Empowerment and Resistance: Motivating Factors of Women Participation in the 1990-People's Movement of Nepal - Acharya, Chiranjivi (Journal of Development Review, 2025)
Nepalese women have actively participated in all political movements in Nepal, both before and following the establishment of democracy. Their contribution, however, is often undervalued. This paper elucidates the specific instances of participation by women in the 1990 People's Movement of Nepal, based on data collected from a dozen female participants, and examines the factors contributing to their involvement. It asserts that women participated in these movements not just for women's issues, but for the freedom of all Nepalese people. The paper posits that women’s desire for equality and justice was linked to a broader vision of human freedom, rather than specific agendas. The overarching desire for common freedom emerged as a significant reason, as women participants emphasized that true liberty could not be an agenda for any single group. They viewed the struggle for freedom as a collective human concern, placing the liberation of all before their own. Many joined the movement, recognizing the historical context where global transitions to democracy intensified the urgency for change in Nepal. Influenced by political parties and leaders, women engaged in the movement, believing that political action was essential for social change. They articulated that only through collective effort could oppressive structures be dismantled, enabling women to enhance their societal status and advocate for wider agendas, ultimately fostering greater equality and empowerment.